On-the-job stress and challenges faced by police personnel of Bishnupur district in COVID-19 times - Nameirakpam, Dipabali; Jupitar, Sanasam; Laishram, Jalina; Soubam, Christina; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: The pandemic has created unprecedented challenges for law enforcement agencies. Police officers are often directly or indirectly involved in the pandemic response and have a higher risk of getting the infection. Our study aims to assess on-the-job stress and challenges faced by the police personnel of Bishnupur district, Manipur, and to determine the factors associated with it. Methods: A cross-sectional study was conducted among the police personnel from December 2020 to January 2021. Occupational stress was measured using the Operational Police Stress Questionnaire and, a pre-tested questionnaire for coping mechanisms and attitude were used to collect data by interview method. Data were analyzed using descriptive statistics, t-test, and ANOVA. 73.2% of them have experienced moderate to high stress and the maximum was found among the Sub-inspectors (Mean score: 3.51±1.20). Stress was mostly due to not having enough time available to spend with friends and family (3.58±2.01), and work overtime (3.27±1.84). Police personnel agreed that there was an increased number of violent confrontations between the public and them while enforcing new regulations and restrictions. The majority of the participants have been accepting the reality of the fact that it has happened and learn to live with it as a coping mechanism. Conclusions: Occupational stress is high among the police personnel of Bishnupur District and it was significantly associated with age, marital status, social stigma, and willingness to take the COVID-19 vaccine. There is a need for holistic support for their job satisfaction.